Characterization of trypanosome isolates from naturally infected horses on a farm in Kenya - Kihurani, D.O.; Masake, R.A.; Nantulya, V.M.; Mbiuki, S.M. (Elsevier, 2000)
Following an outbreak of trypanosomosis in horses on a farm in Kenya, 18 trypanosome isolates were collected from the infected animals over a period of one and a half years and cryopreserved for characterization. The characterization was done on the basis of morphology using Giemsa-stained blood and buffy coat smears, infectivity to mice, recombinant DNA hybridization, and chromosome separation by orthogonal field alternation gel electrophoresis (OFAGE). Morphologically, all the trypanosome isolates were identified as belonging to the subgenus Nannomonas, and a total of 16 out of the 18 isolates grew in mice. Using the recombinant DNA hybridization technique, the isolates were further classified as the 'savannah' type of Trypanosoma congolense. Furthermore, chromosome separation by OFAGE, carried out on six clones derived from different isolates, exhibited a profile characteristic of T. congolense, 'savannah' type. However, there were differences in the number and positions of the medium-sized and minichromosomes indicating a diversity of serodemes within the isolates. Hence the infecting trypanosomes in this disease outbreak were T. congolense, 'savannah' type, and comprised several serodemes or strains.